1999
DOI: 10.1002/(sici)1097-0274(199903)35:3<213::aid-ajim1>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study of mesothelioma in South Africa

Abstract: Background South Africa has, uniquely, mined, transported, and used crocidolite, amosite, and chrysotile. A multicenter case-control Med. 35:213-222, 1999. 1999

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 11 publications
3
31
0
1
Order By: Relevance
“…Rees et al [30] used the same design as in our study A (hospital-based case-control study), but they found a higher AR p close to those estimated in population-based case-control studies. This may be due to the geographical recruitment.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Rees et al [30] used the same design as in our study A (hospital-based case-control study), but they found a higher AR p close to those estimated in population-based case-control studies. This may be due to the geographical recruitment.…”
Section: Resultssupporting
confidence: 59%
“…The proportion of exposed controls was close to that in study A and study B (68% and 57%, respectively) but the proportion of exposed cases was higher than in either study A or B (80% and 87%, respectively). This may account for the value of the estimated AR p found in the study by Rees et al [30] despite its design. …”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…25--27 Some studies have reported that the risk of mesothelioma was significantly affected by the distance of homes to an industrial source of asbestos. 28,29 However, asbestos fibers derived from naturally occurring asbestos may influence larger areas compared with industrial sources. Consequently, the spatial distributions of the mortality rates of mesothelioma and several other cancers caused by naturally occurring asbestos may be significantly different from those caused by industrial sources.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have shown that almost all cases of mesothelioma in South Africa are associated with exposure to crocidolite asbestos (Webster, 1973;Cochrane and Webster, 1978;Rees et al, 1999a;Nolan et al, 2006). Webster considered the association with mesothelioma to be a peculiar property of Cape crocidolite (Webster, 1973).…”
Section: Crocidolitementioning
confidence: 99%